Abdominal obesity and hyperglycemia mask the effect of a common APOC3 haplotype on the risk of myocardial infarction - Ruiz Narváez, Edward A. (2008)
Background: Plasma apolipoprotein (apo) C-III strongly predicts myocardial infarction (MI) and directly activates atherogenic processes in vascular cells. Genetic variation in the insulin response element of the APOC3 promoter is associated with an increased risk of MI. Objective: The objective was to determine whether the APOC3 promoter variation affects plasma apo C-III concentrations and MI only when insulin sensitivity is normal. Design: The APOC3*222 haplotype, defined by the minor alleles of the single nucleotide polymorphisms 3238C→G, −455T→C, and −482C→T, was studied in 1703 matched nonfatal case-control pairs with MI in the Central Valley of Costa Rica. We used fasting hyperglycemia and abdominal obesity as surrogates for insulin sensitivity. Results: The APOC3*222 haplotype was associated with higher apo C-III concentrations only in those with the lowest waist circumference or fasting glucose concentration. The association between the APOC3*222 haplotype and nonfatal MI, previously reported in this population, was strongly influenced by fasting hyperglycemia and abdominal obesity. The odds ratios for MI for the APOC3*222 haplotype were 1.72 (95% CI: 1.16, 2.54) and 1.84 (1.31, 2.59) in subjects in the lowest quintiles of abdominal obesity and fasting hyperglycemia, respectively, and were 0.75 (0.54, 1.05) and 1.16 (0.85, 1.59) in subjects in the highest quintiles, respectively (P for interaction <0.05). Conclusion: The results support the concept that mutations in the APOC3 promoter inhibit the down-regulation of APOC3 expression by insulin. This cardioprotective system becomes dysfunctional in abdominal obesity and hyperglycemia.